Examining transformations in coastal city landscapes: spatial patch analysis of sustainable tourism—a case study in Pahang, Malaysia - Azizan, Marzuki; Milad, Bagheri; Azizul, Ahmad; Tarmiji, Masron; Mohd Fadzil, Akhir (Springer Nature, 2024)
Coastal tourism is crucial for the development of sustainable coastal cities, since it depends on the interaction of natural resources and critical infrastructure. However, handling the complex issues brought on by changing coastal ecosystems and increased visitor expectations calls for a thorough grasp. The Sungai Karang area in Pahang, Malaysia, is used in this paper as a case study to analyze the development phases and transformational effects of coastal resort expansion. Our goal is a detailed assessment of land-use changes brought on by the growing coastline tourist industry. We examine data from 1966 to 2013 using a thorough technique that combines Geographic Information Systems (GIS) with patch analysis. The main findings show dramatic changes in land-use dynamics, with built-up areas increasing by 23.76% and forest cover increasing by 19.35%. Along with an increase in recreational places, utilities and infrastructure also saw a rise of 18.57%. Contrastingly, agricultural regions had a significant decline of 15.43%. These discoveries highlight the significant alteration of the local environment related to beach tourism. Planning effectively and developing coastal cities sustainably need careful observation of the wide-ranging effects that tourist expansion has on the environment, the economy, and society. In conclusion, our study promotes a comprehensive strategy for coastal city government that smoothly integrates with regional goals. This strategy emphasizes quantifiable goals, active community involvement, and preserving both natural and cultural heritage. It highlights the crucial part that careful planning plays in preventing environmental degradation while also acknowledging the difficulties brought on by the tourist industry's explosive growth. In the end, our research highlights the unavoidable necessity of supporting sustainable coastal city development among the varied effects of coastal tourism.